Resilience and Health-Related Quality of Life among Hepatitis C Patients in Pahang, Malaysia (Bangladesh Journal of Medical Science, 2022)
Background: Hepatitis C is one of the most common causes of liver disease worldwide. Health impacts of hepatitis C are not limited to physical morbidity but include psychosocial dimensions such as quality of life (QOL), depression, anxiety, and stigmatization. In Malaysia, modifiable factors that can improve QOL among hepatitis C patients have not been adequately studied. Resilience – defined as the capacity to endure hardships and rebound from life adversities – is associated with mental health and well-being. Our study aims to test the association between resilience and QOL among hepatitis C patients.Methods: Employing a cross-sectional design, 195 hepatitis C patients who attended Hospital Tengku Ampuan Afzan (HTAA) – the main public tertiary hospital in Pahang – were recruited through convenience sampling. Resilience was assessed using the Connor-Davidson resilience scale while Health-Related Quality of Life (HRQOL) was measured by 36-item short-form survey (SF-36v2). Multiple linear regression was run to determine the association between resilience and HRQOL.Results: We found significant associations between resilience and the physical (b=0.35; 95% CI: 0.11, 0.30; p